(المصادر التشريعية اليهودية: (دراسة تحليلية: An Analytical Study of Jewish Legislative Sources - Bensala, Youcef; Ali, Abdul Karim; Mohd Razif, Nor Fahimah (Online Journal of Research in Islamic Studies, 2018)
Knowledge of the legislative sources of any religion is considered the primary outlet for knowing its truth, its legislation, its origins and branches, and the only way to judge its by virtue and validity. A judgment of the thing is part of its conception and can only be imagined by looking at its source. Some religions facilitate access to its sources while others do not so that others are forbidden access. This is the case for Judaism. This study explores the legislative sources of Judaism. The research adopts a historical, library and analytical approach. It concludes that Jews refer to four sources, two of which are accessible to all, namely the Torah and the Talmud, while two have limited access and are not readily available to non-Jews, namely the Protocols and the Apocrypha. Many Jews regard the Talmud as the primary source of Jewish laws followed by the Torah of Moses (the Old Testament) peace be upon him.